Development of the Oxyacetylene Welding Process for PEI/Glass Fiber Laminates - Oliveira, V. S.; Lucas, R. R. [UNESP]; Carvalho, T. P. [UNESP]; Marques, L. F. [UNESP]; Reis, J. F. [UNESP]; Abrahao, A. B. R. M.; Botelho, E. C. [UNESP] (Amer Welding Soc, 2021)
The technology for joining thermoplastics through welding offers numerous advantages over mechanical joining. Currently, the joining of composite parts with weight reduction and cost savings is being developed to improve aircraft performance. This paper proposes the use of oxygen acetylene as a process for bonding composite materials. Oxyacetylene welding is a simple and economical method that can be suitable for polymeric materials. The advantage of applying this technique is a more accessible process that is composed of a portable system with low cost. In evaluating the welding efficiency for composite materials, the lap shear strength (LSS) mechanical test stands out among the most referenced essays in the literature. This work aimed to study the development of oxyacetylene flame welding as well as the optimization of welding parameters for polyetherimide/glass fiber composite. The optimization was performed using complete factorial planning 22 as a tool, and the variables studied were time and distance of the flame. With the optimized condition set as the response variable with the highest lap shear value, the joints obtained were measured for their quality by means of end-notched flexure mechanical testing, thermal analysis, and fracture analysis after LSS testing using optical and electronic microscopy.
Keywords: Composites; Factorial Planning; Hybrid Welding; Oxyacetylene; Manufacturing; Aluminum